Smart marriage contracts : the future of blockchain in matrimonial property law? - Sisák, Ľuboslav (Array, 2021)
This paper is intended to serve as an introductory treatise on the subject of smart marriage contracts (SMC) as a manifestation of blockchain in matrimonial property law of contracts. It starts with a description of the origin and functioning of an SMC from a technical standpoint, while evaluating the legal nature thereof at the same time. Afterwards, we focus on the possibilities and means of an SMC"s establishment under German, Austrian, and Slovak law. Moving on, issues related to the content of a marriage contract establishing an SMC are examined. Then it is tested the permissibility of an SMC-related provision in a marriage contract referred to as a "registration clause". Finally, it is delved into the question whether the appearance of an SMC in a marriage contract introduces any peculiarities to issues of private international law, namely from the perspective of the EU Regulations on property regimes of international couples.